Implementation of Government Policy on the Distribution of Professional Allowances for Local Civil Servant Teachers Directly to Teachers' Accounts at the Secretariat of the Directorate General of Teachers, Educational Personnel, and Teacher Education Ministry of Primary and Secondary Education - Hasoloan, Dean Leonard; Zainal, Veitzhal Rivai; Hakim, Azis (Dinasti Publisher, 2026)
The change in policy to distribute Teacher Professional Allowances directly is a concrete step by the government to simplify bureaucracy and guarantee teachers' rights. Teachers, as the spearhead of education, gain certainty and protection of their rights to professional allowances, enabling them to perform their duties optimally and sustainably. This policy is expected not only to improve teachers' welfare but also to be part of a better, more transparent, and accountable education governance reform. The research method used was descriptive qualitative. The research instruments were interviews, observation, and documentation. There were five informants in this study, all of whom were from within the organization. The results of the study show that the policy of distributing Regional Civil Servant Teacher Professional Allowances (TPG) directly to teachers' accounts aims to improve the efficiency, transparency, and timeliness of payments. With this new mechanism, teachers are expected to receive their allowances faster and more reliably, which will have a positive impact on their welfare and motivation, although it requires strong coordination between the central and regional governments to validate teacher data and accounts. Eliminating bureaucratic procedures through local governments will make the process faster and more accountable. Ensuring that teachers receive allowances regularly, ideally every month along with their salaries. Improving teachers' welfare, which is expected to increase their work enthusiasm and the quality of education.